Implementation of Open and Close a Housing Gate Portal Using RFID Card - Mutiara Sari, Ria; Sabna, Eka; Wahyuni, Refni; Irawan, Yuda (Universitas Muhammadiyah Yogyakarta, 2021)
A safe and conducive home area is one of the things that every resident of housing expects was studied by roy[1]. Portal gate is one of the infrastructure that supports the security of a residential area was studied by irawan[1]. The implementation of the gate portal in Widya Graha I housing, Pekanbaru at this time is still done manually by the security and the application is not optimal because the portal is still often left open by the security. With the development of technology, it is necessary to have an automation system in using the gate portal so that the gate portal can be used more optimally. In designing an automatic gate portal using Arduino as the main controller for the gate portal, Arduino will send commands to the DC motor to open or close the gate portal with an RFID card as the opening of the portal and an infrared sensor as a portal cover, as a fingerprint detection sensor and Arduino as a controlling medium control data input processor. From the test results, the portal will be closed when the vehicle passes through the infrared sensor at a certain distance.